Estimation of Fetal Weight by Johnson’s Formula, Ultrasound and after Delivery (Medical Forum Monthly, 2024)
Objective: The ultimate objective of this study was to assess and validate the accuracy of fetal weight measurement by using Johnson’s formula and its comparison with fetal weight estimated by using ultrasound.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Obstetrics and Gynecology Department, Nishtar Hospital Multan from May 2016 to April 2017.Materials and Methods: In this trial total number of 369 pregnant mothers were included and systematic random sampling was used for selection of mothers. First mother was selected randomly. All the data entered and analyzed by computer software SPSS 23.2. The value of P=0.005 considered to be significant.Results: A total number of 100% (n=369) women were included in this study. The mean age, parity, height and weight of the patients was 29.12±4.02 years, 2.86±1.5 parity, and 149.9±3.94 cm and 51.86±3.86 kg respectively. The study population comprised of 60.4% (n=223) illiterate and 39.6% (n=146) literate women. The age distribution showed 62.3% (n=230) women between 21-30 years 37.7% (n=139) between 31-40 years. There were 54.2% (n=200) women with height 140-150 cm and 45.8% (n=169) between 151-160 cm. It was observed that there were 36% (n=133) women had weight between 40-50 kg and 64% (n=236) had weight between 51-60 kg. There were 66.1% (n=244) women had parity between 1-3 and 33.9% (n=125) had parity between 4-6.The Johnson’s formula was seen to over-estimate the fetal weight. To check the equality of means weight, one way ANOVA was applied, it was seen that all the variables i.e. Johnson’s formula, ultrasound and actual weight had the different means with significant p-value i.e. 0.000 having F-value 18.08.Conclusion: We can conclude from this study that the fetal weight estimated by Johnson’s formula is overestimated while ultrasound estimation of fetal weight always is near to actual weight after delivery.